Exchange Rate (MIS-) Alignment: An Application of the Behavioural Equilibrium Exchange Rate (beer) Approach to Zimbabwe (1990-2018) - Pasara, Michael Takudzwa; Mugwira , Vincent (International Journal of Economics and Financial Issues, 2023)
This study employed the behavioral equilibrium exchange rate (BEER) approach to establish whether or not there is an exchange rate (mis-)alignment in Zimbabwe. The country is characterized by strong and significant deviations between the official and parallel exchange rates and high inflationary pressures which result in macroeconomic and financial instability leading to dwindled economic growth. Among others, the BEER model analysed the significance of macroeconomic variables in influencing exchange rates and also assessed episodes (or states) of over- and under valuation of the currency. The results indicate that all variables except investment (INV) are significant in explaining the BEER. These variables are terms of trade (TOT) which include price of gold, capital flows (CAP) and government spending (GOV) are all highly significant at the 1% level whilst trade openness (OPEN) is weakly significant at the 10% level. The results also indicate that episodes of over-valuation outweighed and outnumbered episodes of under-valuation during the study period 1980 to 2018. The study concludes that exchange rate volatility may originate from factors other than macro fundamentals given the split system that exist between the official and unofficial (parallel) exchange rates. Thus, in addition to correct regulation of macro variables, there is also need to build trust in order to curb speculation, corruption and arbitrage behaviors which amplify distortions.